Instruments used in psychological assessment in the treatment of Obesity: an integrative review (Research, Society and Development, 2022)
The instruments used in psychological assessment in the clinical or surgical treatment of obesity have great relevance in the assessment result and process. Identifying personality, anxiety, depression and binge eating is essential, as they are factors that can directly affect weight maintenance and treatment adherence. The aim of this research was to analyze the scientific literature on instruments used in the psychological assessment of obese people. This is an integrative review carried out in the following databases: BVS, Medical Subject Headings (MeSH), from the National Library, with the following controlled descriptors: "psychometrics", "psychological test", "Psychological Assessment", "psychologist", "obesity", "overweight" and the uncontrolled descriptor "psychological assessment" and the Boolean operators "OR" and "AND". At the end of the searches, 14 publications met the analysis criteria and were selected for the study. From the selected studies, we found 52 tools used in the evaluation, among them, the most used in weight loss programs were, respectively, the Beck Depression Inventory – BDI (Beck Depression Inventory); the Binge Eating Scale - BES (Periodic Binge Eating Scale - TCAP); and the Hospital Anxiety and Depression Scale – HADS. This research provides us with important evidence for the development of specific instruments for the treatment of obesity in Brazil.